Randomized clinical trial of a digital integrative medicine intervention among patients undergoing active cancer treatment - Jun J. Mao; Karolina Bryl; Erin F. Gillespie; Angela Green; Tony K. W. Hung; Raymond Baser; Katherine Panageas; Michael A. Postow; Bobby Daly (npj Digital Medicine)
Abstract Exercise and mindfulness-based interventions have growing evidence for managing fatigue and comorbid symptoms; however, packaging them in a cohesive digital way for patients undergoing cancer treatment has not been evaluated. We conducted a randomized controlled trial to assess the impact of a 12 week digital integrative medicine program, Integrative Medicine at Home (IM@Home), versus enhanced usual care on fatigue severity (primary outcome), comorbid symptoms and acute healthcare utilization (secondary outcomes), in 200 patients with solid tumors experiencing fatigue during treatment. Fatigue severity decreased more in IM@Home than in the control (1.99 vs. 1.51 points; p = 0.04). IM@Home participants also had reduced symptom distress (p = 0.003), anxiety (p = 0.03), and depression (p = 0.02). Acute healthcare utilization was lower with IM@Home, with fewer emergency department visits (rate ratio 0.49; p = 0.04), hospitalizations (4% vs. 12.9%; p = 0.03), and shorter hospital stays (4.25 vs. 10 days; p < 0.001). These promising findings should be confirmed in phase III clinical trials. “Study registered at clinicaltrials.gov (NCT05053230) on 09-20-2021”.